Pathogenic Variants in CHEK2 Are Associated With an Adverse Prognosis in Symptomatic Early-Onset Breast Cancer - Greville-Heygate, Stephanie L. (JCO Precis Oncol, 2020)
PURPOSE: Checkpoint kinase 2 (CHEK2) is frequently included in multigene panels. We describe the associated outcomes among carriers of CHEK2 pathogenic variants in young patients with symptomatic breast cancer. PATIENTS AND METHODS: Participants (N = 2,344) in the Prospective Outcomes in Sporadic Versus Hereditary Breast Cancer study had a diagnosis of primary invasive breast cancer at age ≤ 40 years. Summary statistics were used to compare tumor characteristics among CHEK2+ carriers with those who were CHEK2−. Kaplan-Meier curves were used to demonstrate overall survival (OS) and distant disease-free survival. RESULTS: Overall, 53 of the 2,344 participants (2.3%) had a pathogenic CHEK2 variant. CHEK2+-associated tumors were significantly more likely to be grade 2, estrogen receptor and progesterone receptor–positive compared with CHEK2− tumors (grade 2, n = 28 of 52 [53.8%] v n = 803 of 2,229 [36.0%]; P = .029). CHEK2-associated tumors were significantly more likely to have nodal involvement (N1, n = 37 of 53 [69.8%] v 1,169 of 2,253 [51.9%]; P = .0098) and demonstrated a trend toward multifocality. A higher proportion of participants with CHEK2+ variants with invasive breast cancer were obese than were those with CHEK2− variant (28.3% v 18.8%; P = .039). Univariate and multivariable analyses revealed that OS and distant disease-free survival were significantly worse in CHEK2+ versus CHEK2− carriers (OS hazard ratio, 1.58; 95% CI, 1.01 to 2.48; P = .043). CONCLUSION: This work highlights the adverse prognosis associated with breast cancer in carriers of CHEK2 pathogenic variants. It also identifies a potential association among obesity, family history, and breast cancer risk in young CHEK2 gene carriers.